Organization and identity - Linstead, Alison, 1971-; Linstead, Stephen, 1952- (Routledge, 2005)
The contributors to the collection bring approaches from current philosophising into the area of organization theory and critically assess their relevance and impact.
Keywords: Identity (Psychology) -- Social aspects.; Identité (Psychologie) -- Aspect social.; PSYCHOLOGY -- Social Psychology.; Identity (Psychology) -- Social aspects